Is There a Typology of Teacher and Leader Responders to CALL, and Do They Cluster in Different Types of Schools? A Two-Level Latent Class Analysis of CALL Survey Data. Issue 4 (April 2017) - Bowers, Alex J.; Blitz, Mark; Modeste, Marsha E.; Salisbury, Jason; Halverson, Richard
Background: Across the recent research on school leadership, leadership for learning has emerged as a strong framework for integrating current theories, such as instructional, transformational, and distributed leadership as well as effective human resource practices, instructional evaluation, and resource allocation. Yet, questions remain as to how, and to what extent, teachers and leaders practice the skills and tasks that are known to be associated with effective school leadership, and to what extent do teachers and leaders agree that these practices are taking place in their school. Purpose of the Study: We examine these issues through applying a congruency-typology model to the validation sample of the Comprehensive Assessment of Leadership for Learning (CALL), (117 schools across the United States, including 3, 367 teachers and their school leaders) to examine the extent to which there may be significantly different subgroups of teacher and leader responders to the survey, how these subgroups may cluster nonrandomly in schools, and to what extent the subgroups of teachers and principals are aligned or not on their perception that the skills and practices of leadership for learning take place in their school. Research Design: We used multilevel latent class analysis (LCA) to identify significantly different types of teacher and leader responders to CALL, including a cross-level interaction to examine the extent to which there is a typology model of teacher responders across schools and the extent to which the teacher subgroup responses align with the leader of the school. Findings: We find that there are three statistically significant different subgroups of teacher responders to CALL, low (31.4%), moderate (43.3%), and high (25.4%). In addition, these subgroups cluster nonrandomly across three different types of schools: schools with low leadership for learning (40.2%), moderate leadership for learning (47.0%), and the smallest subgroup, schools with high leadership for learning (12.8%). Conclusions: Our findings suggest that a congruency-typology model of leadership for learning is useful for understanding the context of practice, as schools may be on a continuum of practice in which there is strong alignment between teacher and leader responder types in the low and high schools—indicating problematic or beneficial contexts—but that leaders in the moderate type may be working to move their school towards instructional improvement through leadership for learning. As a quantitative phenomenology, this study provides a rich contextual analysis of the relationship between teachers and leaders on a multisource feedback survey of leadership for learning in schools.